Developing the leather industry in Bangladesh. - Hong, Soon Chan (ADB Briefs, 2018)
This brief examines the benefits, priorities, and possible strategies for developing the leather industry in Bangladesh. To shift the country economy to a higher growth trajectory and sustain high economic growth, the manufacturing and export bases need to be diversified. Leather is one of the industries with considerable potential for development, using Bangladesh large supply of lowcost labor and raw material. The industry has the potential to participate in global value chains, enter a new market, and serve the growing domestic demand. With its abundance of labor and natural resources and successful development experiences in the ready-made garments industry, Bangladesh is ideally suited for the production of leather such as high-value leather goods and footwear.